MY Ole-Ole Application / Nur Asiyah Noor Arifin … [et al.] - Noor Arifin, Nur Asiyah; Santong, Stellycia; Bidie@James, Hariena; Jalil, Nur Nafijah; Tangit, Tania Maria (Faculty of Computer and Mathematical Sciences, 2022)
Souvenirs play a very important role in tourism. These memorabilia represent a connection to people, places and including events. More often than not, customers will go around to different shops to compare souvenir items, which is time-consuming. As an alternative, MY Ole-Ole, an eCommerce site provides souvenir shopping within customers' fingertips. MY Ole-Ole is an e-Commerce platform dedicated to serving as a one-stop souvenir centre for tourists. This virtual store provides a wide range of Malaysian souvenir products, ranging from food to fabric items, which can be delivered or collected in-store. The aim of MY Ole-Ole is to provide customers the opportunity to select local souvenir items according to preferences and location. The target users of this mobile application are Malaysians purchasing local souvenir items as corporate gifts, as well as international tourists visiting Malaysia for leisure and MICE activities. Among the unique features of MY Ole-Ole are its speedy (same-day) delivery and the ability to filter gifts based on preferences (e.g., age, gender, product type, packaging, etc). This application also encourages customers to select and consider souvenirs according to their budget and preferences without any hassle. MY Ole-Ole will benefit local SMEs by extending the reach of their products to a wider market. Overall, the MY Ole-Ole a useful application for its user to easily search and compare souvenirs as it saves time and convenient to use.